English - Jovanović, Ksenija; Trailović, Ranko; Mutavdzic, Perica; Tomić, Ivan; Sladojević, Miloš; Dimić, Andreja; Dragaš, Marko; Kočar, Igor; Davidović, Lazar (Medical Research, 2022)
Introduction: Neuromuscular blockade reversal may provoke cardiovascular events. We present a case of a middle-aged, vascular patient in whom ventricular tachycardia and hypertensive crisis occurred immediately after the initiation of neuromuscular blockade reversal. Patient Review: A 56-year-old man was admitted to our Institution for emergency surgical treatment of left extremity ischemia. Besides hypertension, the patient’s medical history was negative for any other significant acute or chronic diseases. Routine preoperative analyzes, ECG, and echocardiography showed normal findings. The patient underwent urgent transpopliteal thrombectomy under general endotracheal anesthesia. Immediately following the initiation of neuromuscular blockade reversal, with a diluted mixture of atropine and neostigmine (1 mg/2.5 mg, respectively), ventricular tachycardia and hypertensive crisis developed. Arterial blood gas analyses and electrolyte values ​​were within the reference limits at the moment. Adequate therapeutic measures were undertaken immediately, and sinus rhythm was restored shortly. Later, serial ECG records showed negative T waves in the precordial leads, with an increasing trend of troponin I values ​​(ranging from 0.59 to 5.45 μg/L). Coronary angiography was later performed and revealed a normal coronary angiogram. During the next three days, ischemic ECG alterations showed resolution and the patient was hemodynamically stable. On the fifth postoperative day, the patient was discharged, in good general medical condition. Conclusion: A careful administration of the atropine/neostigmine mixture is advised. Malignant arrhythmias must be recognized and treated promptly by an anesthesiologist, in order to achieve positive treatment outcomes.